1995
DOI: 10.1074/jbc.270.21.12774
|View full text |Cite
|
Sign up to set email alerts
|

Direct Association of Grb2 with the p85 Subunit of Phosphatidylinositol 3-Kinase

Abstract: Phosphatidylinositol 3-kinase (PI 3-kinase) has been shown to play a key role in growth factor signaling pathways, although its signaling mechanism has not been fully elucidated. Using the yeast interaction trap system, we have identified Grb2 as a PI 3-kinase interacting protein. Our experiments demonstrate that p85, the regulatory subunit of PI 3-kinase, interacts with Grb2 in vivo, and this interaction is independent of growth factor stimulation. The direct association between Grb2 and p85 was reconstituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 45 publications
4
67
1
Order By: Relevance
“…It is unclear how the appearance of PI 3-kinase activity in anti-phosphotyrosine immunoprecipitates correlates with the level of PI 3-kinase product lipids in whole cells: the maximal amount of PI 3-kinase activity found in antiphosphotyrosine immunoprecipitates is only 4% of that which can be detected in anti-p85a immunoprecipitates. Despite reports of an inducible association between p85 and Shc in Bcr-Abl transformed chronic myelogenous leukemia cells (Harrison-Findik et al, 1995) and constitutive association between p85 and Grb2 in ®broblasts (Wang et al, 1995), we were unable to detect PI 3-kinase activity in Shc immunoprecipitates (data not shown). It has been suggested that a 115 kDa tyrosine phosphoprotein of unknown identity can associate with p85 following NGF treatment of PC12 cells (Ohmichi et al, 1994): this may account for PI 3-kinase activity in anti-phosphotyrosine immunoprecipitates.…”
Section: Discussioncontrasting
confidence: 67%
“…It is unclear how the appearance of PI 3-kinase activity in anti-phosphotyrosine immunoprecipitates correlates with the level of PI 3-kinase product lipids in whole cells: the maximal amount of PI 3-kinase activity found in antiphosphotyrosine immunoprecipitates is only 4% of that which can be detected in anti-p85a immunoprecipitates. Despite reports of an inducible association between p85 and Shc in Bcr-Abl transformed chronic myelogenous leukemia cells (Harrison-Findik et al, 1995) and constitutive association between p85 and Grb2 in ®broblasts (Wang et al, 1995), we were unable to detect PI 3-kinase activity in Shc immunoprecipitates (data not shown). It has been suggested that a 115 kDa tyrosine phosphoprotein of unknown identity can associate with p85 following NGF treatment of PC12 cells (Ohmichi et al, 1994): this may account for PI 3-kinase activity in anti-phosphotyrosine immunoprecipitates.…”
Section: Discussioncontrasting
confidence: 67%
“…Therefore, signaling of PI 3-kinase through its speci®c phosphoinositide lipid products may remain intact and activate various downstream targets such as protein kinase C isomers, ras and akt (Carpenter and Cantley, 1996;Hemmings, 1997;Toker and Cantley, 1997). As in wildtype p85b the BCR-homology region of the chimeric protein could interact with the GTPbound forms of rac and Cdc42 (Carpenter and Cantley, 1996), while its proline-rich region and SH3 domain could bind abl, lck, lyn, fyn, dynamin, a, b and g tubulin, p36/38, GRB2, actinin, SHC, src, cbl, phosphoinositides and p85 to itself (Kapeller et al, 1994;1995;Pleiman et al, 1994;Gout et al, 1993, Susa et al, 1996Fukazawa et al, 1995;Wang et al, 1995;Shibasaki et al, 1994;Harrison-Findik et al, 1995;Liu et al, 1993;Meisner et al, 1995). Membrane localization of PI 3-kinase, either via N-terminal myristoylation or via C-terminal farnesylation signals, is su cient to stimulate downstream targets (Klippel et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This is because in addition to binding to Sos, Grb2 can use its SH3 domain to bind to other proline-rich containing proteins, such as PI3 kinase (Wang et al, 1995), and Grb2-associated binder protein-1 (Gab-1) (HolgadoMadruga et al, 1996). Both PI3 kinase and Gab-1 can stimulate Akt activity (Holgado-Madruga et al, 1997;Wang et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is because in addition to binding to Sos, Grb2 can use its SH3 domain to bind to other proline-rich containing proteins, such as PI3 kinase (Wang et al, 1995), and Grb2-associated binder protein-1 (Gab-1) (HolgadoMadruga et al, 1996). Both PI3 kinase and Gab-1 can stimulate Akt activity (Holgado-Madruga et al, 1997;Wang et al, 1995). The activation of Akt by PI3 kinase or Gab-1 appears to be Ras-independent because the binding of Grb2 to PI3 kinase or Gab-1 can exclude Sos from binding to Grb2, and could potentially stimulate Akt activity without stimulating Erk1,2 activity (Holgado-Madruga et al, 1997; Wang et al, 1995).…”
Section: Discussionmentioning
confidence: 99%